Insights Into Development and Progression of Idiopathic Pulmonary Fibrosis From Single Cell RNA Studies - Nemeth, Julia; Schundner, Annika; Frick, Manfred (Frontiers in Medicine, 2020)
Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal lung disease with limited therapeutic options. The current model suggests that chronic or repetitive “micro-injuries” of the alveolar epithelium lead to activation and proliferation of fibroblasts and excessive extracellular matrix (ECM) deposition. Disruption of alveolar type II (ATII) epithelial cell homeostasis and the characteristics of mesenchymal cell populations in IPF have received particular attention in recent years. Emerging data from single cell RNA sequencing (scRNAseq) analysis shed novel light on alterations in ATII cell progenitor dysfunction and the diversity of mesenchymal cells within the fibrotic lung. Within this minireview, we summarize the data from most recent human scRNAseq studies. We aim to collate the current knowledge on cellular plasticity and heterogeneity in the development and progression of IPF, effects of drug treatment on transcriptional changes. Finally, we provide a brief outlook on future challenges and promises for large scale sequencing studies in the development of novel therapeutics for IPF.